2007
DOI: 10.2987/8756-971x(2007)23[190:eopapg]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pyrethrin and Permethrin Ground Ultra-Low Volume Applications for Adult Culex Control in Rural and Urban Environments of the Coachella Valley of California

Abstract: Six experimental ground ultra-low volume (ULV) applications of Pyrenone 25-5 (0.0025 lb/acre) and Aqua-Reslin (0.007 lb/acre) were made by truck-mounted Pro-Mist or London Fog equipment over 1-mi2 study areas in rural and residential environments of the Coachella Valley, Riverside County, California. Efficacy of replicate applications was evaluated by measuring mortality among caged sentinel mosquitoes, by evaluating changes in host-seeking abundance at replicated dry ice-baited traps positioned along intersec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Pyrethroids are more stable in light and air than natural pyrethrins. Today, they are one of the most widely used domestic and agricultural pesticides (Heudorf and Angerer, 2001;Lothrop et al, 2007), they are used to control pests in residential and agricultural settings, to treat head lice and scabies in humans and fleas in pets, for public health vector control, and for disinfection of commercial aircrafts (AnadĂłn et al, 2009(AnadĂłn et al, , 2013aWei et al, 2012;USEPA, 2013). Pyrethroid insecticides account for more than 30% of insecticides used worldwide (Barr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroids are more stable in light and air than natural pyrethrins. Today, they are one of the most widely used domestic and agricultural pesticides (Heudorf and Angerer, 2001;Lothrop et al, 2007), they are used to control pests in residential and agricultural settings, to treat head lice and scabies in humans and fleas in pets, for public health vector control, and for disinfection of commercial aircrafts (AnadĂłn et al, 2009(AnadĂłn et al, , 2013aWei et al, 2012;USEPA, 2013). Pyrethroid insecticides account for more than 30% of insecticides used worldwide (Barr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors including environmental conditions have a significant impact upon the efficacy of aerosols used in adult mosquito control operations; for instance, hotarid climates are likely to be particularly problematic because of impacts such as rapid evaporation. No studies have been identified that look at the performance of thermal fog in hot, dry conditions; however, ground and aerial ULV aerosol pesticide delivery in hot dry conditions has been carried out with mixed outcomes against desert locusts (Holland and Jepson 1996) and mosquitoes (Lothrop et al 2007a, Lothrop et al 2008, in part because of population dynamics or wind conditions at the time of delivery. No studies have been identified that investigate differences in success of ULV or thermal fog (or ULV and thermal fog side by side) applications in hot, dry compared to warm, moist conditions, regardless of wind conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrethroid insecticides, a group of synthetic insecticides, are widely used in agriculture and public health programs worldwide (Heudorf and Angerer, 2001;Lothrop et al, 2007). Their availability for consumer use in the household has increased since the early 2000s (US Environmental Protection Agency, 2005) when restriction on use of organophosphorus pesticides (OPs) in residential environments in the United States was imposed (US Environmental Protection Agency, 1998).…”
Section: Introductionmentioning
confidence: 99%